Cumulative deceleration area: a simplified predictor of metabolic acidemia. (2nd October 2021) - Furukawa, Abby; Neilson, Duncan; Hamilton, Emily
Abstract: Objective: Fetal monitoring, ubiquitous in obstetrics is used to predict and prevent intrapartum fetal injury. Despite decades of education and nomenclature revision, clinicians show low agreement on key elements, including the types of deceleration and hence their presumed etiology. Cumulative deceleration area is not dependent on deceleration type and could potentially mitigate this problem. Although deceleration area has shown promise as a marker of acidemia, no reports have shown how deceleration area evolves in late labor. Advances in computerization allow for direct measurement of deceleration area and standard fetal heart rate (FHR) patterns. The objective of this study was to compare the evolution and discrimination performance of deceleration area and other FHR patterns in late labor in term neonates with metabolic acidemia (MA) and in those with normal cord gases. Methods: This retrospective cohort study included women with a term singleton (≥37 weeks) in cephalic presentation with cord gas data and FHR tracings available for analysis. MA included neonates with an umbilical artery base deficit >12 mmol/L ( n = 132). Controls included those with normal cord gases (base deficit <8 mmol/L) and a 5-minute Apgar score of >6 ( n = 1498). Deceleration area and other FHR patterns were summarized and compared in 30-minute segments over the last five hours. Receiver-operating characteristic curves were constructed and AUCs compared. Results: Deceleration area had the highest AUC (0.702, 95% CI 0.655–0.749) and was a superior marker of MA compared to baseline (AUC 0.588, 95% CI 0.530–0.645), baseline variability (AUC 0.611, 95% CI 0.558–0.663), and number of late decelerations (AUC 0.582, 95% CI 0.527–0.637). Conclusion: Cumulative deceleration area reduces the necessity to determine deceleration type. In a single number, it objectively quantifies three important aspects of decelerations; frequency, depth and duration and was a superior marker of MA compared to baseline level, baseline variability and number of late decelerations. The acidemia group had higher deceleration area over the last two hours prior to delivery. This result indicates that the cumulative area and persistence of repetitive decelerations is important clinically.